Update on the Recommended HBV Screening in the United States - Kong, MD, Xuejun; Li, MD, Mark; Hu, MD, Ke-Qin (North American Journal of Medicine and Science, 2011)
Hepatitis B virus (HBV) infection is a serious public health problem that can be associated with HBV-cirrhosis and hepatocellular carcinoma (HCC). HBV-related chronic liver disease is particularly prevalent in the Asian population with significant disparity. Although convenient HBV screening and diagnosis tests are safe and effective, HBV vaccination have been available for many years, under-screening and under-diagnosis of HBV infection is still a serious problem in the USA and worldwide. This article systemically reviewed effectiveness of universal HBV vaccination programs that have been implemented in many countries and regions, the facts of HBV under-screening in the U.S., especially in Asian Americans, and the updated recommendations of HBV screening and vaccination by Center of Disease Control and Prevention (CDC).